Salivary Mucocele Secondary to Parotid Duct Obstruction by Grass in a Dog - Mallmann Pozzobon, Franciéli; da Silva Reinstein, Rainer; Domingues Mörschbächer, Priscilla; Cristina Basso, Paula; Veloso Brun, Maurício; Curvello de Mendonça Müller, Daniel (Acta Scientiae Veterinariae, 2024)
Background: Salivary mucocele results from the accumulation of saliva secondary to salivary gland or duct injury. Its etiology remains poorly understood, with limited reports on the parotid gland. Some of the causes include duct rupture due to trauma, bite wounds, or obstructions due to mineralized calculi (sialoliths) or foreign bodies. The complete excision of the gland-duct complex is currently the most indicated treatment. Thus, this study aimed to report the diagnosis and treatment of a dog with salivary mucocele caused by a parotid duct rupture due to bahiagrass (Paspalum notatum) obstruction. Case: A 4-year-old male Belgian Shepherd Malinois dog weighing 31.5 kg, intact, was treated by the clinical staff of the University Veterinary Hospital of the Federal University of Santa Maria (UFSM) for swelling on the left and part of the right face, which was initially attributed to an interaction with insects. The dog did not manifest pain or derangement in physiological parameters, such as blood count or biochemical test results. Physical examination of the skin was unremarkable. The dog was hospitalized and initially clinically treated with steroidal anti-inflammatory, antimicrobial, and antihistamine drugs and responded satisfactorily. However, after 18 days, recurrence was noted and the animal was brought in for care and was again responsive to steroidal anti-inflammatory and antimicrobial drugs. Fine-needle aspiration cytology showed mixed and pyogranulomatous inflammation. Culture and antibiogram tests showed no significant microbiological growth. The dog underwent surgical exploration 12 days after recurrence, which showed presence of a fibrous connective tissue capsule, confirmed via histopathology. A new recurrence was noted 5 days after surgical removal, with viscous fluid collection in the subcutaneous tissue draining through the incision line. A new surgical procedure showed intense proliferation of granulation tissue, with a segment of bahiagrass (Paspalum notatum) identified in the subcutaneous tissue, close to the parotid duct. Due to the initial absence of facial lesions, we deduced that the grass migrated upwards, probably orally, causing an important tissue reaction that resulted in duct rupture. To confirm the rupture, a surgical thread was introduced through the ostium of the salivary duct until it reached the proliferative tissue. Due to the impossibility of completely dissecting the gland, only one lobe of the parotid gland was excised and the ruptured salivary duct was closed, and the tissues were sutured. Discussion: To the authors’ knowledge, no other cases of parotid duct rupture induced by grass culminating in the partial surgical excision of the gland has been documented. There is a report citing ductal stenosis and treatment by duct excision, maintaining the entire parotid gland, which is different from the present report. Although rare, parotid gland mucocele due to duct rupture has been reported with an identified cause. Some authors suggest the complete excision of the gland-duct complex as a treatment, while others suggest ligation only of the proximal parotid duct, with no signs of recurrence. This technique avoids the risk of iatrogenic injury to the facial nerve, closely associated with the gland. In the present case, a complete excision of the parotid gland was not performed by the surgeon, although the procedure was successful. In conclusion, parotid duct rupture can occur in dogs due to a lesion associated with grass of the species Paspalum notatum and should be included as a differential diagnosis of salivary mucocele. Keywords: dog, foreign body, mucocele, obstruction, parotid. Título: Sialocele por obstrução do ducto parotídeo por gramínea em cão Descritores: cão, corpo estranho, mucocele, obstrução, parótida.